Data from: Multifrequency study of HH 137 and HH 138: Discovering new knots and molecular outflows with Gemini and APEX - Ferrero, Leticia V. (2020)
We present reduced H2 and K near-infrared band images of HH 137, taken with the GSAOI+GeMS instrument of the Gemini South telescope. In addition, we provide submilimiter data in 12CO(3-2), 13CO(3-2), C18O(3-2), HCO+(3-2) and HCN(3-2) molecular lines of both HH 137 and HH 138, obtained with the SHeFI instrument of the Atacama Pathfinder EXperiment (APEX) telescope.